Magnetic resonance-guided focused ultrasound thalamotomy for essential tremor patients with low skull density ratio: a case-matched analysis - Ng, Patrick R.; Blitz, Sarah E.; Chua, Melissa M. J.; Cosgrove, G. Rees (Frontiers in Neurology, 2024)
Introduction Skull density ratio (SDR) is the ratio between the mean Hounsfield units of marrow and cortical bone, impacting energy transmission through the skull. Low SDR has been used as an exclusion criterion in major trials of magnetic resonance-guided focused ultrasound (MRgFUS) thalamotomy for medication-refractory essential tremor (ET). However, some studies have suggested that patients with low SDR can safely undergo MRgFUS with favorable outcomes. In this case-matched study, we aim to compare the characteristics, sonication parameters, lesion sizes, and clinical outcomes of patients with low SDR vs. patients with high SDR who underwent unilateral MRgFUS thalamotomy for medication-refractory ET. Methods Between March 2016 and April 2023, all patients (n = 270) who underwent unilateral MRgFUS thalamotomy for medication-refractory ET at a single institution were classified as low SDR (<0.40) and high SDR (≥0.40). All clinical and radiological data was prospectively collected and retrospectively analyzed using non-case-matched and 1:1 case-matched methodology. Results Thirty-one patients had low SDR, and 239 patients had high SDR. Fifty-six patients (28 in each cohort) were included in 1:1 case-matched analysis. There were no significant differences in baseline characteristics between the two groups in both non-case-matched and 1:1 case-matched analyses. In both analyses, compared to patients with high SDR, patients with low SDR required a significantly higher maximum sonication power, energy, and duration, and reached a lower maximum temperature with smaller lesion volumes. In the non-case-matched and case-matched analyses, low SDR patients did not have significantly less tremor control at any postoperative timepoints. However, there was a higher chance of procedure failure in the low SDR group with three patients not obtaining an appropriately sized lesion. In both analyses, imbalance was observed more often in high SDR patients on postoperative day 1 and month 3. Discussion ET patients with SDR <0.40 can be safely and effectively treated with MRgFUS, though there may be higher rates of treatment failure and intraoperative discomfort.